Bridging Care Transition After Hospitalization for Atrial Fibrillation and Coronary Interventions. Issue 3 (March 2022) - Hijazi, Yosef; Karkabi, Basheer; Feldman, Marina; Malca, Bruria; Lavi, Idit; Jaffe, Ronen; Schliamser, Jorge E.; Shiran, Avinoam; Flugelman, Moshe Y.
Abstract : Abstract: Treatment fragmentation between hospitals and the community can result in catastrophic outcomes; uninterrupted treatment with anticoagulant and platelet aggregation inhibitors is particularly important. We assessed the proportion and characteristics of patients who did not visit their primary community-based physician within 1 week of discharge from our department of cardiovascular medicine and the proportion that failed to procure essential drugs at the community pharmacy. We prospectively studied 423 patients who were discharged from our department. They were provided detailed explanations, tablets for 7 days, prescriptions, and a printed drug plan. We traced the time from discharge until a visit with a primary community-based physician, and the time until the procurement of medications, using our computerized community–hospital–integrated system. Complete data were available for 313 patients, of whom 220 were treated with anticoagulants or platelet aggregation inhibitors. For 175 patients, these drugs were initiated during index hospitalizations. Only 1 patient did not receive platelet aggregation inhibitors despite recommendations. Seventy-nine patients (25%) first visited their primary care physicians more than 1 week after discharge. Predictors for delayed visits were living alone (hazard ratio 1.91) and having an in-house caregiver (hazard ratio 2.01). In conclusion, all but 1 patient continued drug therapy after discharge from the hospital. The simple predischarge steps included patient education and provision of a 1-week supply of tablets and prescriptions. Treatment continuation was independent of visits to the community-based primary physician. Patients living alone or with an in-house caregiver more often delayed visits to primary physicians yet continued relevant drug therapy.